2018
DOI: 10.1016/j.dib.2018.08.135
|View full text |Cite
|
Sign up to set email alerts
|

Data related to the sinter structure analysis of titanium structures fabricated via binder jetting additive manufacturing

Abstract: The adoption of metal binder jetting additive manufacturing (AM) for functional parts relies on a deep understanding between the materials, the design aspects, the additive manufacturing process and sintering. This work focuses on the relationship between sintering theory and process outcomes. The data included in this article provides additional supporting information on the authors’ recent publication (Wheat et al., 2018 [1]) on the sinter structure analysis of commercially pure titanium parts manufactured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…The results showed that porous cellular Ti structures with variable porosity could be successfully manufactured, with the same mechanical strength behavior under compression stress being achieved. The connection between theory of sintering and process results was the main topic of another work by evan et al [9]. Furthermore, the current study provides further insights into the subject matter, building upon the authors' previous publication [7] which focused on the characterisation of sintered structures in commercially pure titanium components produced by powder bed binder jetting additive manufacturing.…”
Section: Titanium Based Powdersmentioning
confidence: 64%
“…The results showed that porous cellular Ti structures with variable porosity could be successfully manufactured, with the same mechanical strength behavior under compression stress being achieved. The connection between theory of sintering and process results was the main topic of another work by evan et al [9]. Furthermore, the current study provides further insights into the subject matter, building upon the authors' previous publication [7] which focused on the characterisation of sintered structures in commercially pure titanium components produced by powder bed binder jetting additive manufacturing.…”
Section: Titanium Based Powdersmentioning
confidence: 64%
“…Sheydaeian et al investigated the MBJ of CP-Ti, emphasizing the complexities associated with particle segregation during powder deposition and anisotropic shrinkage during sintering [18]. Wheat et al's findings confirmed these challenges, using computer tomography to visualize how particle size distribution affected the density and microstructure of green and sintered CP-Ti samples [19]. Polozov et al attempted to fabricate Ti-22Al-25Nb alloy via the MBJ of mixed elemental powders, high-temperature reactive sintering (800-1100 • C), and subsequent annealing at 1400 • C. The resulting microstructure showcased a B2/β-phase with acicular Ti2AlNb precipitates [20].…”
Section: Introductionmentioning
confidence: 99%